GIS & RS Applications in Simulation of Hydrological Process - Akbari, Abolghasem (2016)
This workshop have been organised to explain the fundamentals and main components of Geospatial Information System (GIS) and Remote Sensing (RS) with emphasis on spatial data structures, map projection and data management tools using ArcGIS. It is also discover the GIS&RS capabilities in extracting physical parameters of watershed in order to support hydrological model using HEC-Geo-HMS and HEC-HMS.